2017
DOI: 10.1177/1049732317721477
|View full text |Cite
|
Sign up to set email alerts
|

What Facilitates “Patient Empowerment” in Cancer Patients During Follow-Up: A Qualitative Systematic Review of the Literature

Abstract: Empowerment is a concept of growing importance in cancer care, but little is known about cancer patients' experiences of empowerment during follow-up. To explore this area, a qualitative systematic literature review was conducted in PubMed, CINAHL, and PsycINFO. A total of 2,292 papers were identified and 38 articles selected and included in the review. The thematic synthesis of the papers resulted in seven analytical themes being identified: empowerment as an ongoing process, knowledge is power, having an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 63 publications
4
62
0
2
Order By: Relevance
“…In healthcare, power, structure and agency shape both staff and patient experiences in different ways; whilst hospital hierarchical systems can be oppressive, they also create patient empowerment [46]. Patient empowerment can be an ongoing process, where active patient roles, information and knowledge, and positive, caring communications with professionals can all empower patients within health systems [47]. These patient experiences have their antecedents in staff well-being and positive working environments, where staff themselves are empowered to enable high quality patient care [3].…”
Section: Realist Social Theory and Powermentioning
confidence: 99%
“…In healthcare, power, structure and agency shape both staff and patient experiences in different ways; whilst hospital hierarchical systems can be oppressive, they also create patient empowerment [46]. Patient empowerment can be an ongoing process, where active patient roles, information and knowledge, and positive, caring communications with professionals can all empower patients within health systems [47]. These patient experiences have their antecedents in staff well-being and positive working environments, where staff themselves are empowered to enable high quality patient care [3].…”
Section: Realist Social Theory and Powermentioning
confidence: 99%
“…In the presentation round, participants will share information about their background and cancer diagnosis, and they will be encouraged to use selected picture cards to narratively describe their expectations and desired outcomes of participation. The aim of the session is to enhance group formation and to establish a sense of community among participants since this may facilitate patient empowerment [45]. Central staff members (course leader, physician, clinical dietitian, and evening hostess) participate.…”
mentioning
confidence: 99%
“…Although it could be argued that this challenge is grounded in overly broad inclusion criteria, several studies considered such inclusiveness a strength, emphasising the added value of including research that did not explicitly investigate barriers and facilitators [17,24]. Conversely, several studies reported the lack of explicit focus on barriers and facilitators within the primary literature as a limitation to their synthesis [53][54][55].…”
Section: Methodological Issues In Conducting Barrier and Facilitator mentioning
confidence: 99%